The Effect of Incentives and Work Satisfaction on Employee Loyalty in the New Normal Period - Gama, Andhika Apta Putra; Santoso, Bowo (CV. Rayyan Dwi Bharata, 2022)
This study aims to see the effect of employee incentives and job satisfaction on employee loyalty in the new normal period after the Covid-19 pandemic takes place. This study used the object of study, namely the Amaris Hotel. The respondents in this study were all employees at the Amarism Hotel Surabaya with a total of 50 respondents who were processed using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of this study show that incentives have an original sample value of 0.609 with a significance of 0.000 (0.05) which means that incentives have a positive and significant influence on employee loyalty. In addition, job satisfaction has an original sample value of 0.371 with a significance of 0.000 (0.05) which means that job satisfaction has a positive and significant influence on employee loyalty.